African origin of human-specific polymorphic Alu insertions. - Batzer, M A (1994)
Alu elements are a family of interspersed repeats that have mobilized throughout primate genomes by retroposition from a few "master" genes. Among the 500,000 Alu elements in the human genome are members of the human-specific subfamily that are not fixed in the human species; that is, not all chromosomes carry an Alu element at a particular locus. Four such polymorphic human-specific Alu insertions were analyzed by a rapid, PCR-based assay that uses primers that flank the insertion point to determine genotypes based on the presence or absence of the Alu element. These four polymorphic Alu insertions were shown to be absent from the genomes of a number of nonhuman primates, consistent with their arising as human genetic polymorphisms sometime after the human/African ape divergence. Analysis of 664 unrelated individuals from 16 population groups from around the world revealed substantial levels of variation within population groups and significant genetic differentiation among groups. No significant associations were found among the four loci, consistent with their location on different chromosomes. A maximum-likelihood tree of population relationships showed four major groupings consisting of Africa, Europe, Asia/Americas, and Australia/New Guinea, which is concordant with similar trees based on other loci. A particularly useful feature of the polymorphic Alu insertions is that the ancestral state is known to be the absence of the Alu element, and the presence of the Alu element at a particular chromosomal site reflects a single, unique event in human evolution. A hypothetical ancestral group can then be included in the tree analysis, with the frequency of each insertion set to zero. The ancestral group connected to the maximum-likelihood tree within the African branch, which suggests an African origin of these polymorphic Alu insertions. These data are concordant with other diverse data sets, which lends further support to the recent African origin hypothesis for modern humans. Polymorphic Alu insertions represent a source of genetic variation for studying human population structure and evolution.